Loss of Drosophila Clueless differentially affects the mitochondrial proteome compared to loss of Sod2 and Pink1 - Sen, Aditya; Cox, Rachel T. (Frontiers in Physiology, 2022)
Mitochondria contain their own DNA, mitochondrial DNA, which encodes thirteen proteins. However, mitochondria require thousands of proteins encoded in the nucleus to carry out their many functions. Identifying the definitive mitochondrial proteome has been challenging as methods isolating mitochondrial proteins differ and different tissues and organisms may have specialized proteomes. Mitochondrial diseases arising from single gene mutations in nucleus encoded genes could affect the mitochondrial proteome, but deciphering which effects are due to loss of specific pathways or to accumulated general mitochondrial damage is difficult. To identify specific versus general effects, we have taken advantage of mutations in three Drosophila genes, clueless, Sod2, and Pink1, which are required for mitochondrial function through different pathways. We measured changes in each mutant’s mitochondrial proteome using quantitative tandem mass tag mass spectrometry. Our analysis identified protein classes that are unique to each mutant and those shared between them, suggesting that some changes in the mitochondrial proteome are due to general mitochondrial damage whereas others are gene specific. For example, clueless mutants had the greatest number of less and more abundant mitochondrial proteins whereas loss of all three genes increased stress and metabolism proteins. This study is the first to directly compare in vivo steady state levels of mitochondrial proteins by examining loss of three pathways critical for mitochondrial function. These data could be useful to understand disease etiology, and how mutations in genes critical for mitochondrial function cause specific mitochondrial proteomic changes as opposed to changes due to generalized mitochondrial damage.